Postoperative Aqueous Flare in Diabetic Eyes and Fluidics-Related Surgical Parameters After Cataract Surgery Using the Eight-Chop Technique - Tsuyoshi Sato (Journal of Clinical Medicine, 2026)
Objectives: This study aimed to quantify aqueous flare in diabetic eyes after low-stress phacoemulsification and identify factors associated with persistent inflammation. Methods: Eyes undergoing active-fluidics phacoemulsification with the Eight-Chop Technique were assigned to diabetes mellitus (DM) or nondiabetic control groups. Aqueous flare was measured by laser flare photometry preoperatively and at postoperative day 1, day 7, week 7, and week 19. Intraoperative variables (cumulative dissipated energy [CDE], irrigation fluid volume, and operative time) and diabetic retinopathy status were recorded. Mixed-effects models evaluated longitudinal flare changes; multivariable regression identified factors for day 7 flare. Results: A total of 172 eyes (86 DM; 86 controls) from 106 patients were analyzed. Postoperative flare increased in both groups, peaked on day 7, and then declined; diabetic eyes had significantly higher flare throughout. Day 7 flare was higher in diabetic eyes (26.4 vs. 16.3 ph/ms), approximately 39% higher in a patient-clustered analysis (95% CI: 14–70%; p = 0.001). After adjusting for preoperative flare, irrigation fluid volume, CDE, and operative time, diabetic eyes had approximately 25% higher day 7 flare (95% CI: 3–53%; p = 0.026), persisting across time points (interaction p = 0.087), with similar results in a complete-case sensitivity analysis. Within this model, preoperative flare and irrigation fluid volume were significantly associated with higher day 7 flare, whereas cumulative dissipated energy and operative time were not. Conclusions: Under low-stress phacoemulsification, diabetic eyes exhibited persistently higher postoperative aqueous flare. Day 7 flare may indicate persistent barrier dysfunction, and its association with irrigation fluid volume suggests fluidics-related factors in inflammation.